Study Regarding Changes in Decision-Making Process During the Crisis Period - Ranf Diana; Gorski Hortensia (Scientific Bulletin, 2020)
Why the decision? Because we have to make decisions every day, more important or less important decisions that lead our lives in a certain direction, in both cases being necessary to choose between several courses of action. The decision is part of our lives and making the optimal decision is important, whether it comes from managers or from regular individuals. An organizational environment characterized by insecurity, frequent and sudden changes has a negative impact on the management of an organization. Under these circumstances, the reaction to these changes, instabilities materialize in quick, correct decisions that induce organizational stability. The main objective of the article is to analyze the decision-making process within the organizations that constitute the private environment in Sibiu. The question that the article wants to answer is: the expertise (knowledge, theories, methods) of managers in decision making sufficient or does this new context require an adaptation, reorganization of the decision-making process? The article contains a qualitative interview-based investigation, which is the premise of a comprehensive research based on a questionnaire to provide solutions to the problems identified.